2009
DOI: 10.2109/jcersj2.117.32
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field-induced giant strain in Bi0.5Na0.5TiO3-based single crystals: Influence of high-oxygen-pressure annealing

Abstract: Influences of high-oxygen-pressure (350 MPa) annealing on the properties of leakage current, polarization, and strain were investigated for single crystals of (Bi0.5Na0.5)TiO3-(Bi0.5K0.5)TiO3-BaTiO3 with P4mm tetragonal structure The oxygen annealing led to a marked increase in leakage current, showing that the oxidized crystals have a high concentration of electron hole (carrier) and a low concentration of oxygen vacancy compared with the crystals annealed in air. While the air-annealed crystals exhibited a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 90 publications
3
9
0
Order By: Relevance
“…Ren [29] reported the large electro-strain effect in aged BaTiO 3 single crystal, which was similar to our results of OS.Teranishi et al [18] and Noguchi et al [19,21] considered that origin of the large strain in NBT-KBT-BT was reversible rotation of nano-sized 901 domains. In other words, both of them suggested that the defect dipolar pairs connected with oxygen vacancies could be used to explain the reversibility of non-1801 domains, which could produce large electro-induced strain.…”
Section: Electric Propertiessupporting
confidence: 88%
See 2 more Smart Citations
“…Ren [29] reported the large electro-strain effect in aged BaTiO 3 single crystal, which was similar to our results of OS.Teranishi et al [18] and Noguchi et al [19,21] considered that origin of the large strain in NBT-KBT-BT was reversible rotation of nano-sized 901 domains. In other words, both of them suggested that the defect dipolar pairs connected with oxygen vacancies could be used to explain the reversibility of non-1801 domains, which could produce large electro-induced strain.…”
Section: Electric Propertiessupporting
confidence: 88%
“…Besides, it is interesting that a peculiar P-E loop of OS was observed, which was much slimmer than the other two loops. A similar result was obtained in NBT-KBT-BT single crystal after being annealed in air at 950 1C for 10 h [21]. Fig.…”
Section: Electric Propertiessupporting
confidence: 86%
See 1 more Smart Citation
“…Values of d 33 * greater than 1000 pm V −1 were reported in barium titanate‐ and alkali‐niobate‐based families, but the achievable electrostrain is quite low (often below 0.3%) . Single crystals possess remarkable values for both d 33 * and electrostrain, the difficulties in fabrication and associated high cost have yet to be overcome for production in quantity. In this Communication, we report giant electrostrain (0.70%) and d 33 * (1400 pm V −1 ) in a non‐textured lead‐free polycrystalline ceramic.…”
mentioning
confidence: 99%
“…Noguchi et al [14] reported that the association pair composing of oxygen vacancy and A-site vacancy in ferroelectricity of Bi 0.5 Na 0.5 TiO 3 based single crystal affects the ferroelectric properties. Therefore, the polarization measurement was carried out to investigate the dopant-vacancy associates in detail.…”
Section: Resultsmentioning
confidence: 99%